Digital Branding Strategy for Leather Bag Products at the Manding Sabdodadi Bantul Craft Center - Ari Retno Purwanti; Puji Handayani Putri; T Heru Nurgiansah (Journal of Education Technology Information Social Sciences and Health, 2024)
Arum Handycraf leather craftsmen, who are one of the MSMEs in the Manding RT 07 Sabdodadi Bantul Tourism Village area, have experienced a decline in sales and marketing of the products they produce since the pandemic until now. Over time, these MSMEs began to rise slowly in producing and selling products. The purpose of service is to help increase sales by branding the products produced both offline and online. Offline branding includes making advertising designs about products and then published through print and non-print media. Online/digital branding in the form of expanding market share through online marketing, namely Web MSMEs. This service activity is carried out by the method of conducting counseling in the form of training, discussion and question and answer. These service activities include providing knowledge about the importance of product branding to MSME players and digital marketing through the MSME web. The MSME web is made with brand visualization that is in line with the identity of MSMEs and the MSME web that is easy to use by MSME actors. The results obtained in this service activity MSME actors understand the importance of product branding and correct rules, high-quality product photos appear on the MSME web complete with detailed information on goods in the form of skin specifications used and prices. Craftsmen become more able to market products more widely with their characteristics.